Antecedents and Performance Implications of Contracting for Knowledge Workers: Evidence from Information Technology Services - Mayer, Kyle J.; Nickerson, Jack A. (Organization Science, 2005)
This paper develops a theory that predicts why firms organize their knowledge workers as employees versus independent contractors and predicts the performance implications of this choice. It then empirically examines this organizational choice—which our theory predicts will be driven by contracting difficulties arising from expropriation concerns, measurement costs, and interdependence—and its implications for profitability for 190 information technology service projects. Using a two-stage switching regression model, our analysis shows that projects aligned according to our theory are on average more profitable than misaligned projects and that firm capability impacts organizational choice but not profitability.